Removal of phenol from water using ozone - Turhan, Kadir; Uzman, Suheyla (ELSEVIER SCIENCE BV, 2008)
Aromatic compounds are extensively used ill several of industries and call cause pollution ill water Sources. This study aims to examine the degradability of phenol by ring cleavage in aqueous Solutions using ozone and to determine the kinetics. A semi-batch process was employed in this Study. Samples from the reaction medium were taken at certain time intervals, and concentrations of phenol were determined using UV/VIS spectrophotometer. The samples were also Subjected to total organic carbon (TOC) analysis to monitor concentration changes of phenol. The Intermediate products formed during ozonization were determined GUMS.
Keywords: ozone; phenol; aromatic pollutants; advanced oxidation process (AOPs); kinetic; ADVANCED OXIDATION PROCESSES; AQUEOUS-SOLUTION; DEGRADATION; OZONATION; DECOMPOSITION; MECHANISM; KINETICS; Engineering; Water Resources